Skull Base Angle Morphometry in South Indian Population with Review on Terminology - Raveendranath, Veeramani; Dash, Prafulla Kumar; Nagarajan, Krishnan; Kavitha, Thangaraj; Swathi, Srinidhi (Indian Journal of Neurosurgery, 2021)
Introduction Basal angle, Boogaard’s angle, and clival angle are frequently used in diagnosing the craniometric angle malformations either on radiography or now more on MRI. But anatomic and clinical studies have used varied terms for these parameters. We aimed to look for these parameters among a normal south Indian adult population to standardize the measurements and their terminology.Materials and Methods One hundred MRI images (50 males and 50 female) were studied retrospectively. MRI images that were reported as normal by neuroradiologist were taken up for the study. Mean and the standard deviation of males and females were calculated for basal angle, Boogaard’s angle, and clival angle, separately. Unpaired t-test was used to analyze the significant difference (p < 0.05) between the genders. The intraclass coefficient correlation was used to analyze the interobserver variability.Results The mean value of basal angle in males and females are 113°and 114°, respectively. The mean value of Boogaard’s angle in males and females are 120°and 121°, respectively. The mean value of clival angle in males and females are 157°and 155°, respectively. There was no statistically significant difference (p > 0.05) between males and females in all three angles.Conclusion Knowledge about the normal angles will be an important tool in understanding the normal and abnormal skull base. Since the type of skull varies in accordance with race, the normal craniometric angle also varies in accordance with race. The present study tried to standardize the parameters of normal skull base angles for appropriate correction of the anomalies and uniform usage of terminology.
Keywords: basal angle; Boogaard’s angle; clivus-canal angle; magnetic resonance imaging; terminology